PENGGUNAAN DISFEMISME DALAM KASUS PINJAMAN ONLINE DAN DAMPAKNYA TERHADAP PSIKOLOGIS KORBAN: KAJIAN SOSIOPRAGMATIK - Suryalaga, Novan; Azizah, Tresna Nur; David Lengkong, George Fritz; Hendaya, Revalina Annisa; Darmayanti, Nani (Universitas Padjadjaran, 2025)
ABSTRACT. The increasing use of online loan applications each year has led to a rise in the number of online loan borrowers. Based on data from the OJK in April 2025, the number of loan recipient accounts reached around 153.1 million. The increasing number of borrowershas also led to an increase in the number of online loan cases that have a negative impact on the psychological condition of borrowers. One factor affecting the psychological condition of borrowers in online loan cases is the use of harsh words or dysphemisms in collectionmethods. Dysphemism refers to the use of harsh words intended to insult, curse, or belittle. The use of harsh words towards borrowers by debt collectors will certainly have an impact on the psychological condition of borrowers, which is the background of this study. Usingqualitative and semi-quantitative research methods as well as sociopragmatic analysis, this study aims to analyze various forms of dysphemism directed at borrowers. In addition, there are also psychological effects such as anxiety disorders, stress, depression, and suicidal tendencies. There are also social dysfunction and physical effects such as chest tightness, headaches, and increased stomach acid. Keywords: online loans, dysphemism, psychology, harsh words, sociopragmatic.